Synthesis and relationship of stability and biological activity of new DSS and TMP conjugates. Issue 4 (22nd December 2014) - Sun, Yewei; Tan, Zicheng; Liang, Zhibin; Wang, Liang; Shan, Luchen; Yu, Pei; Lee, Simon MingYuen; Wang, Yuqiang
Abstract : A series of novel conjugates of danshensu (DSS) and tetramethylpyrazine (TMP) were designed and synthesized. Abstract : A series of novel conjugates of danshensu (DSS) and tetramethylpyrazine (TMP) were designed and synthesized. Their stability toward hydrolysis by carboxylesterase and cardioprotective effect against t -BHP- and doxorubicin-induced damage were evaluated in H9c2 cells. The results revealed that increasing steric hindrance with bulky groups at the linkage position between DSS and TMP prolonged the half-life and also markedly increased the protective effect. Compound7 was the most potent in protecting against t -BHP- and doxorubicin-induced damage. The protective effect of compound7 may in part be attributed to its promotion of mitochondrial biogenesis.